Generation of Atomic Optical Lattices by Dammann Gratings. (17th April 2012) - Ji, Xianming; Xu, Shuwu; Gu, Songbo
Abstract : We first calculated the diffraction intensity distributions of the Dammann gratings illuminated by Gaussian light wave. The empirical equations were deduced by numerical calculations to calculate the parameters, such as the spatial period, the maximum intensity, and the maximum intensity gradient, of the optical trap array composed by a set of Dammann gratings and a focus lens. Thus, a novel type of optical trap array for trapping cold atoms (or molecules) was proposed and its features were discussed. The results showed the optical trap array with very short period could be generated. High optical dipole potential could be presented so as to have strong attractive force to the atoms to form atomic optical lattices of high lattice density. Compared with the optical lattices formed by standing wave interferences of CO2 laser, there are many unique advantages of which are formed by Dammann gratings.